Rediscovery of Acilepis anaimudica (B.V. Shetty & Vivek.) Kottaim. (Asteraceae), A Threatened Endemic Species of Western Ghats, India - Murugan, Perumal; Kottaimuthu, Ramalingam; Sujana, Kanjiraparambil Arjunan; Sharief, Mohamed Umer (Indian Forester, 2023)
No Abstract.